Tanggung Jawab Pemilik Konten yang Mengunggah Ulang Video di Jejaring Media Sosial Menggunakan Prinsip Penggunaan Wajar menurut Undang-Undang Nomor 28 Tahun 2014 tentang Hak Cipta - muhammad Ifqie Dzikrullah; Efridani Lubis; Fauziah Fauziah (Jurnal Hukum Jurisdictie, 2021)
This thesis discusses the responsibility of content owners who re-upload videos on social media networks. This thesis is motivated by the large number of re-uploaders making content creators nervous because a content creator has made a video with great effort. Many YouTubers have appealed to "against" re-uploaders by not watching their videos, but even with the appeal there are still many actors who re-upload them in cyberspace. The formulation of the problem in this thesis is about How Law No.28 of 2014 concerning Copyright regulates re-uploading of video content networked by social media and How is the responsibility of content creators who re-uploaders to the original owner of content networked by social media. This type of research is library research which then collects and studies data that comes from books, literature, scientific journals, legal documents related to the object of research. The results of this study explain that the perpetrator's responsibility to deactivate the account is as done by the perpetrator of a fatal re-upload as was done by the Malik Tube Youtube channel which uploaded all the contents of the Dalang Pelo channel. Because there were many negative comments and received a warning from Youtube, the content was finally deactivated permanently. The conclusion of this thesis is that regarding the responsibility of content creators who are proven to re-upload at this time only apologies to their personal social media, and delete the content from their accounts and even deactivate the account forever.